Статеві особливості сенсомоторної функції осіб молодого віку з урахуванням моторної асиметрії = Gender features of sensorimotor function in young people with motor asymmetry - Romanchuk, Alexander P; Guziy, Oksana V; Glushchenko, Marina N (Journal of Education, Health and Sport, 2016)
Romanchuk A. P., Guziy O. V., Glushchenko M. N. Статеві особливості сенсомоторної функції осіб молодого віку з урахуванням моторної асиметрії = Gender features of sensorimotor function in young people with motor asymmetry. Journal of Education, Health and Sport. 2016;6(1):38-63. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44575 http://ojs.ukw.edu.pl/index.php/johs/article/view/44575 http://pbn.nauka.gov.pl/works/690437 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. СТАТЕВІ ОСОБЛИВОСТІ СЕНСОМОТОРНОЇ ФУНКЦІЇ ОСІБ МОЛОДОГО ВІКУ З УРАХУВАННЯМ МОТОРНОЇ АСИМЕТРІЇ 1Романчук О. П., 2Гузій О. В., 1Глущенко М. М. 1Південноукраїнський національний педагогічний університет ім. К.Д. Ушинського 2Львівський державний університет фізичної культури GENDER FEATURES OF SENSORIMOTOR FUNCTION IN YOUNG PEOPLE WITH MOTOR ASYMMETRY 1Romanchuk A. P., 2Guziy O. V., 1Glushchenko M. N. 1South Ukrainian National Pedagogical University n.a. K.D. Ushinsky 2L’viv State University Physical Culture Анотація З використанням приладу «Комп’ютерний вимірювач рухів» були обстежені 745 практично здорових осіб молодого віку (середній вік складав 21,4±2,6 років), з них 493 чоловіки та 252 жінки. Дослідження статевих особливостей сенсомоторної функції з урахуванням моторної асиметрії дозволило встановити, що найбільш вірогідними (р<0,05) визначались відмінності у виражено ліворуких жінок, які стосувались центральних (за показником ПЦУ), підкоркових (за показником ТЦР) та медулярних (за показником ЧРС) механізмів організації рухів. Серед результатів дослідження вагомими виявилися дані, які свідчать про поліноміальну залежність між показниками влучності правою та лівою рукою з урахуванням моторної асиметрії, як у чоловіків, так і у жінок. Ключові слова: стать, сенсомоторна функція. Abstract We have examined 745 healthy young adults aged 21,4±2,6 (including 493 men and 252-women) by using the appliance «Computer movements measurer». Having investigated the sexual features of sensor-motor function taking into account the motor asymmetry we have found that the most likely (p<0,05) differences between the central (switch of central units), subcortical (movement cycle durability) and medullary (reaction time to light) mechanisms of movements appear in left-handed women. The significant results show that there is the polynomial relationship between the left and right hand accuracy measures by taking into account the motor asymmetry in both men and women. Keywords: gender, sensorimotor function.